Designing and Developing a Combined Program based on the Theory of Mind Method and the Floortime Method and its Effectiveness on Social-Communication Skills and Stereotypical Behaviors of Children with Autism Disorder - Kargar Ghanatalnuj , Mahdiyeh; Shahriari , Mansure; Tajali , Parisa (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present research was conducted with the aim of designing and compiling a combined program based on the theory of mind method and the flortime method and its effectiveness on social-communication skills and stereotyped behaviors of children with autism spectrum disorder. Method: The present research method is mixed (qualitative-quantitative) of sequential exploratory type. In the qualitative part with the approach of inductive content analysis, socio-statistics included all the valid scientific sources and articles indexed and related in the databases, and theoretical sampling and the saturation rule were used. In the quantitative part, the population of this research was all children aged 2 to 5 years with autism spectrum disorder who referred to Autism Center of Rafsanjan, who were willing to cooperate and participate in the meetings on behalf of themselves and their families. The sample included 5 children aged 2 to 5 years with autism spectrum disorder. These people were selected by purposeful sampling and investigated in a single-group study with a single-subject design. The research tool was Gilliam Gazer’s (1994) questionnaire. Results: The results of the qualitative part of the research led to the development of a 12-session combined therapy package based on the theory of mind method and flortime method. The results of the quantitative part showed that the combined training method based on the theory of mind method and the flortime method had an effect on the social-communication skill components with an improvement percentage between 25 and 55%. The theory of mind method and the Flortime method have had an effect on the scores of stereotyped behaviors with a recovery percentage between 14 and 46%. Conclusion: The conceptual model of the combined program based on the theory of mind method and the flortime method was developed based on the dimension of communication skills, the dimension of motor speech skills, the dimension of interpersonal skills and social interaction, and the dimension of emotion recognition. The results showed that the teaching method of the combined program based on the theory of mind method and the flortime method had an effect on social-communication skills and stereotyped behaviors